Analisis Jangkauan Layanan Halte Trans Metro Pasundan Terhadap Lokasi Perguruan Tinggi di Wilayah Bandung Raya - Indrianawati Indrianawati; Sumarno Sumarno; Tedy Imanuel Selan (Jurnal Serambi Engineering, 2023)
Efforts to improve the quality of Trans Metro Pasundan services can be carried out by determining the coverage area of Trans Metro Pasundan bus stops. One way is by analyzing the coverage area of TMP bus stops towards the locations of universities located in the Bandung Raya region. The method used for this analysis of TMP bus stop coverage towards university locations is the network analyst service area method. The coverage radius for TMP bus stop services is determined based on the maximum walking distance from and to the TMP bus stop, which is 400 meters and 800 meters. The analysis results show that out of 124 universities in the Bandung Raya region, 31 universities are within the coverage area of TMP bus stops within a 400-meter radius, and 45 universities are within the coverage area of TMP bus stops within an 800-meter radius. An analysis of the coverage capability of bus stops towards universities shows that the Bandung Accounting Academy is the university most accessible by TMP bus stops, with a total of 8 bus stops within a 400-meter radius and 13 bus stops within an 800-meter radius.